Preoperative walking exercise to improve prognosis in patients with supratentorial brain tumours after craniotomy: protocol for a randomised controlled trial - Jun Zhou; Fangkun Liu; Zhixiong Liu; Chunrun Qu; Zeng Cao; Shihan He (BMJ Open, 2024)
Introduction Cardiopulmonary complications and cognitive impairment following craniotomy have a significantly impact on the general health of individuals with brain tumours. Observational research indicates that engaging in walking is linked to better prognosis in patient after surgery. This trial aims to explore whether walking exercise prior to craniotomy in brain tumour patients can reduce the incidence of cardiopulmonary complications and preserve patients’ cognitive function.Methods and analysis In this randomised controlled trial, 160 participants with supratentorial brain tumours aged 18–65 years, with a preoperative waiting time of more than 3–4 weeks and without conditions that would interfere with the trial such as cognitive impairment, will be randomly assigned in a ratio of 1:1 to either receive traditional treatment or additional combined with a period of 3–4 weeks of walking exercise of 10 000–15 000 steps per day. Wearable pedometer devices will be used to record step counts. The researchers will evaluate participants at enrolment, baseline, 14 days preoperatively, 3 days prior to surgery and 1 week after surgery or discharge (select which occurs first). The primary outcomes include the incidence of postoperative cardiopulmonary complications and changes in cognitive function (gauged by the Montreal Cognitive Assessment test). Secondary outcomes include the average length of hospital stay, postoperative pain, participant contentment, healthcare-associated costs and incidence of other postoperative surgery-related complications. We anticipate that short-term preoperative walking exercises will reduce the incidence of surgery-related complications in the short term after craniotomy, protect patients’ cognitive function, aid patients’ postoperative recovery and reduce the financial cost of treatment.Ethics and dissemination The study protocol has been approved by Ethics Committee of Xiangya Hospital of Central South University (approval number: 202305117). The findings of the research will be shared via publications that have been reviewed by experts in the field and through presentations at conferences.Trial registration number NCT05930288.